Effects of nitrogen, phosphorus, and potassium base fertilizers on growth and yield of Taraxacum kok-saghyz Rodin - W. Zhang; F. Zheng; D. Wei; G. Shen; X. Zeng; N. G. Kon’kova (Труды по прикладной ботанике, генетике и селекции)
Taraxacum kok-saghyz (TKS) is a promising natural rubber plant. In the current study we investigated effects of nitrogen, phosphorus, and potassium base fertilizers on growth and yield of TKS through the field experiments. We found that appropriate application of nitrogen, phosphorus, and potassium base fertilizers can significantly increase root, rubber and total sugar yield of TKS. The TKS rubber yield enhanced significantly when the amount of nitrogen and phosphorus, potassium increased accordingly to 107.2, 10.5 and 35.3 g m–2. Maximum accumulation of rubber in the TSK roots is caused by application of potassium fertilizer.According to the obtained results the recommended amount of base fertilizers under conditions of Harbin Experimental Station (N45.592729°, E126.581668°) is 107.2 g m–2 of urea, 43.4 g m–2 of calcium superphosphate, 10.5 g m–2 of potassium chloride.